1988
DOI: 10.1093/jee/81.2.476
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Effects of Pesticides on the Parasitoid Aphytis melinus (Hymenoptera: Aphelinidae)

Abstract: Sublethal effects of insecticides on the parasitoid Aphytis melinus DeBach were investigated. Longevity, daily rate of progeny production per female, and size and sex ratio of offspring were measured for parasitoids exposed to rates near the LC,;s of carbaryl, chlorpyrifos, dimethoate, malathion, and methidathion. Survivorsof the exposure to carbaryl exhibited no significantsublethal effects.Exposure to each of the organophosphorous materials reduced longevity by 73-85% and temporarily depressed progeny produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 17 publications
2
30
1
Order By: Relevance
“…Croft (1990) reported that more than 75% of the studies from 1950 to 1986 measured mortality of beneficial insects, while median lethal dose, concentration, or time were measured in another 20% of the studies; only 5% of the studies reported sublethal effects. The sublethal effects reported mostly are reduced fecundity and longevity (Grosch, 1970(Grosch, , 1975O'Brien et al, 1985;Hsieh and Allen, 1986;Rosenheim and Hoy, 1988). Studies, such as the present one, that also monitor altered foraging behavior of beneficial insects as a result of insecticide exposure, are rarely performed, even though this is a key behavior for beneficial insect effectiveness.…”
Section: Discussionmentioning
confidence: 90%
“…Croft (1990) reported that more than 75% of the studies from 1950 to 1986 measured mortality of beneficial insects, while median lethal dose, concentration, or time were measured in another 20% of the studies; only 5% of the studies reported sublethal effects. The sublethal effects reported mostly are reduced fecundity and longevity (Grosch, 1970(Grosch, , 1975O'Brien et al, 1985;Hsieh and Allen, 1986;Rosenheim and Hoy, 1988). Studies, such as the present one, that also monitor altered foraging behavior of beneficial insects as a result of insecticide exposure, are rarely performed, even though this is a key behavior for beneficial insect effectiveness.…”
Section: Discussionmentioning
confidence: 90%
“…females emerge with a fraction of the eggs that can potentially be matured during a lifetime. The evidence for synovigeny in Aphytis comes from (1) comparisons between initial egg loads (Opp & Luck, 1986;Rosenheim & Rosen, 1991, 1992Collier et al, 1994;Heimpel et al, 1994Collier, 1995;Heimpel & Rosenheim, 1995) with reports of lifetime reproductive success (Quednau, 1964;Gulmahamad & DeBach, 1978;Rosenheim & Hoy, 1988;Luck, 1990), and (2) dissections showing that egg maturation occurs after eggs have been laid Collier, 1995). Previous studies have also shown that a single complement of eggs can be matured without host feeding (see refs.…”
Section: Discussionmentioning
confidence: 99%
“…The lifespan of sugar-fed Aphytis females varies between 2 and 6 weeks (DeBach & White, 1960;Bartlett, 1962;Quednau, 1964;Avidov et al, 1970;Gulmahamad & DeBach, 1978;Rosenheim & Hoy, 1988;Takagi & Ogata, 1990;Heimpel et al, 1994;Heimpel & Rosenheim, 1995;Collier, 1995). In contrast, the lifespan of sugar-deprived females rarely exceeds three days (Avidov et al, 1970), whether or not host feeding is allowed (DeBach & White, 1960;Heimpel et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The indirect effects of pesticides on natural enemies (Table 1) have not been studied as extensively compared to direct effects, and those studies associated with indirect effects of pesticides have primarily involved evaluating fecundity and longevity [23][24][25][26][27].…”
Section: Indirect Effects Of Pesticides On Natural Enemiesmentioning
confidence: 99%
“…Although indirect effects may be more subtle or chronic compared to direct effects [14,[28][29] any indirect effects may inhibit the ability of natural enemies to establish populations; suppress the capacity of natural enemies to utilize prey; impact parasitism (for parasitoids) or consumption (for predators) rates; decrease female reproduction; reduce prey availability; inhibit ability of natural enemies to recognize prey; influence the sex ratio (females: males); and reduce mobility, which could impact prey-finding [3,27,[30][31]. In addition, more than one physiological and/or behavioral parameter may be indirectly affected after exposure to a pesticide.…”
Section: Indirect Effects Of Pesticides On Natural Enemiesmentioning
confidence: 99%